Measured and perceived food environment influences on women’s nutritional health in marginalized areas of northern Mexico: a structural equation modeling analysis - Zahid García; Juan Martín Preciado Rodríguez; Gloria Elena Portillo Abril; Alma Delia Contreras Paniagua; María Isabel Ortega-Vélez (Frontiers in Public Health)
BackgroundObesity is a growing global public health problem and a risk factor for developing non-communicable diseases (NCDs). The food environment is crucial in shaping nutritional behaviors and health outcomes. However, how food environment indicators interrelate and impact the population’s health in middle- and low-income countries is unclear. This study examined the association between the food environment and indicators of obesity and NCDs in adult women from medium and high-marginalization areas in Hermosillo, Northwest Mexico.MethodsA randomized sample of 104 adult women and 80 food retail stores participated in this cross-sectional study. Data on diet, anthropometric measurements, and NCD diagnoses were collected. We assessed the food environment’s personal (perceived) and external (measured) dimensions. Personal dimensions included perceived accessibility, affordability, convenience, and desirability of foods, while external dimensions comprised the variety, prices, density of food establishments, and advertising presence in participants’ neighborhoods. Data were collected via questionnaires and inventories and analyzed using geospatial and structural equation modeling (SEM) techniques to explore the relationships between food environment indicators and health outcomes.ResultsThe participants, with an average age of 47.6 years, exhibited an average BMI of 31.0 kg/m2, a high prevalence of abdominal obesity (90%), and NCDs (40%). The food environment in these areas was characterized by a high density and variety of food establishments offering unhealthy food options. Participants also perceived prices of healthy foods as high and reported exposure to advertising promoting unhealthy foods. Structural equation modeling revealed that a more nutritious food environment, as indicated by the perception of availability and lower prices of healthy foods, was negatively associated with waist circumference (β: −0.37, p < 0.05) and indirectly with the prevalence of NCDs (β: 0.30, p < 0.05).ConclusionOur findings contribute to the empirical evidence that food environments influence the nutritional health of vulnerable populations. The results suggest that public policies should focus on improving the food environment by enhancing the availability and affordability of healthy foods.